TECHNOLOGICAL TRANSFORMATION OF LEARNING MEDIA IN THE DIGITAL ERA: A COMPREHENSIVE ANALYSIS OF IMPACT, CHALLENGES, AND IMPLEMENTATION IN INDONESIA - Nuke Septembriana Lestari Hastuti; Rini Fitriana; Dian Yuningsih; Apriliantoni (STMIK Indonesia Banda Aceh, 2026)
The education sector plays a vital role in imparting religious, secular, and social knowledge. Technological advancements have transformed educational methods, evolving from the use of stone inscriptions to the boundless digital era. Instructional media has shifted from handwriting and computers to touchscreens, driving rapid innovation in the field. Electronic media—ranging from slide projectors, overhead projectors (OHP), and LCDs to Digital Interactive Boards (DIB)—have streamlined the teaching and learning process. This evolution warrants a closer look at how instructional media technology has developed and the advantages digital media offers over conventional alternatives. Consequently, this article aims to explicitly examine the evolution of instructional media technology in education and identify the key advantages of digital media over conventional media. It employs a literature review and observational analysis of media evolution—spanning from the era of inscriptions to the digital age—with a specific focus on electronic media from the early 1980s to the present. The analysis reveals that these advancements have enhanced the speed, ease, and accuracy of content delivery: image-based media foster a unified understanding of the material among students; text-based media reduce the time teachers spend writing manually; and modern digital media, such as DIBs and touchscreens, provide intuitive interfaces that facilitate comprehension through natural movement and habits, rather than requiring strenuous cognitive effort. In conclusion, the evolution of instructional media technology has significantly impacted the efficiency and effectiveness of the teaching and learning process. Given their superiority in terms of ease of use, speed, accuracy, and intuitiveness, digital media are recommended for wider adoption in modern schools.